(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
We present a case of 35 years old women who presented to our institution with a history of bilateral infiltrating duct cell carcinoma of breast, chest pain with heaviness, severe respiratory distress and hypotension. Echocardiography revealed massive pericardial effusion with features of cardiac tamponade. The patient was treated with urgent pericardiocentesis followed by subxiphoid pericardial window drainage of 500ml of haemorrhagic pericardial fluid. Cytological examination confirmed the previous suspicious of malignancy. The patient tolerated the procedure very well, immediate symptomatic relief was observed.